Preparation method and application of functional lithium battery positive electrode AT9 coating additive material

By introducing additives with gas adsorption function into the AT9 coating of the positive electrode of the lithium battery, the problem of bulging of the lithium battery is solved, and the effective capture of the gas inside the battery is achieved, cost is reduced and battery performance is maintained.

CN119504596AInactive Publication Date: 2025-02-25安徽得壹能源科技有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411631921.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The problem of lithium battery bulging causes abnormal internal pressure of the battery, which may cause fire or explosion, and the existing technology solutions are costly and affect battery performance.

Method used

By introducing additives with gas adsorption function into the AT9 coating of the positive electrode of the lithium battery, functional AT9 coating additive materials are prepared by using Fuker alkylation reaction, nucleophilic substitution reaction and ion exchange reaction to effectively capture the gas inside the battery.

Benefits of technology

Effectively capture gases that may be generated inside the battery without affecting the overall performance of the battery, simplifying solutions to prevent battery bloating and reducing related costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005136136930000051
    Figure BDA0005136136930000051
  • Figure BDA0005136136930000061
    Figure BDA0005136136930000061
  • Figure HDA0005136136940000011
    Figure HDA0005136136940000011
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a functional lithium battery positive electrode AT9 coating additive material. The method comprises the following steps: S1, carrying out preheating treatment on p-benzyl bromide and an alkylation reagent, then adding a catalyst, and carrying out Friedel-Crafts alkylation reaction to obtain a porous precursor; s2, dissolving the porous precursor and imidazole bromide in a solvent, and carrying out nucleophilic substitution reaction to obtain an imidazole modified porous precursor; and S3, placing the imidazole modified porous precursor in an alkali solution, and carrying out an ion exchange reaction to obtain the functional lithium battery positive electrode AT9 coating additive material. The material prepared by the method has the function of enriching carbon dioxide in battery swelling gas, relieves gas swelling pressure in the battery, and can overcome the defects of high cost, influence on battery performance and the like in the conventional battery swelling prevention technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium batteries, and in particular to a preparation method and application of a functional lithium battery positive electrode AT9 coating additive material. Background Art

[0002] The bulging problem of lithium batteries is one of the key challenges that need to be solved in the battery field. Its causes are complex and diverse, mainly including electrolyte decomposition, overcharge and overdischarge, natural aging, and physical damage. These factors lead to an abnormal increase in the internal pressure of the battery, which in turn causes the battery shell to swell, which we call "lithium battery bulging". Lithium battery bulging is not only an appearance problem, but also a serious safety hazard. The internal pressure of the bulged battery is abnormal, and harmful gases such as hydrogen, oxygen and carbon dioxide may be produced. Among them, carbon dioxide, as an important gas component, not only increases the internal pressure of the battery, but also may participate in the chemical reaction inside the battery, further accelerating the aging and damage of the battery. More seriously, when the bulging battery is subjected to external impact or internal short circuit, these gases may react with oxygen in the air, causing serious accidents such as fire or even explosion, which seriously threatens personal and property safety. Therefore, the research and solution of the bulging problem of lithium batteries is of great practical significance.

[0003] In the battery industry, preventing lithium battery bulging is a crucial issue. In order to meet this challenge, the industry has adopted a variety of innovative strategies. Starting from the process manufacturing level, by introducing the open formation process, the gas generated by the battery during the manufacturing process can be discharged in time, effectively avoiding the bulging phenomenon caused by internal gas accumulation.

[0004] For example, patent application CN114284562A designed a new type of open-cell formation method, which simplified the traditional battery open-cell formation method. Through vacuum liquid injection, open pre-charge activation, and three-stage charging formation and sealing, it reduces gas production and improves battery cycle stability. Starting from the level of battery cell structure design, optimizing the explosion-proof valve design is also an important measure. It can automatically release gas when the internal pressure of the battery rises abnormally, thereby preventing the battery from bulging or even exploding.

[0005] For example, patent CN116259920B has designed a double-layer explosion-proof valve structure, which achieves graded pressure relief by setting valve plates with different valve opening pressures. The first-level valve plate quickly responds to initial gas production, while the second-level valve plate responds to extreme situations. The double protection prevents battery explosion and improves overall safety without increasing the total pressure relief area. Starting from the material level, the selection of more stable positive and negative electrode materials and electrolytes that are not easy to decompose can control gas generation from the source, which is of great significance for improving the overall safety and reliability of the battery.

[0006] For example, patent application CN105810997A innovatively uses cyclic and chain ether solvents, combined with inorganic lithium salt additives, to effectively inhibit chemical decomposition and gas production, improve the high-rate charge and discharge cycle stability of lithium titanate batteries, avoid flatulence, and enhance battery performance. All of the above methods can effectively alleviate battery gas production and reduce the risk of battery bulging. However, these methods often involve more complex battery design changes, which may affect the actual performance of the battery, require the replacement of instruments and equipment in actual production, and invest a lot of design effort and long-term experimental sample verification work, making the cost of use high and difficult to promote.

[0007] Therefore, exploring a simple, economical anti-bulging design solution that does not sacrifice battery performance is crucial to solving the battery bulging problem. Summary of the invention

[0008] The AT9 component in lithium batteries, specifically the ceramic protective layer coated on the edge of the positive electrode, is an indispensable and key part of lithium battery technology. This ceramic edge is designed on the edge of the positive electrode material to significantly improve the safety, performance stability, thermal tolerance and corrosion resistance of the battery. Its main composition is based on a series of oxide materials, including core components such as zirconium titanate, lithium titanate, boehmite and alumina, supplemented by trace amounts of dispersants and sintering aids to ensure the uniformity and density of the coating. Changing the additives of AT9 does not require the replacement of special equipment in the process, and will not affect the basic performance of the battery to a certain extent during use. By innovatively incorporating additives with gas adsorption functions into the ceramic edge formula, this design achieves effective capture of gases that may be generated inside the battery without affecting the overall performance of the battery, thereby simplifying the solution to prevent battery bulging problems and reducing related costs.

[0009] In one aspect of the present invention, the present invention provides a method for preparing a functional lithium battery positive electrode AT9 coating additive material. According to an embodiment of the present invention, the method comprises:

[0010] S1: preheating p-dibrombenzyl and an alkylating agent, then adding a catalyst to perform a Friedel-Crafts alkylation reaction to obtain a porous precursor;

[0011] S2: dissolving the porous precursor and imidazole bromide in a solvent, and performing a nucleophilic substitution reaction to obtain an imidazole-modified porous precursor;

[0012] S3: placing the imidazole-modified porous precursor in an alkaline solution to perform an ion exchange reaction to obtain a functional lithium battery positive electrode AT9 coating additive material. The material prepared by this method has the function of enriching carbon dioxide in the battery bulging gas, relieving the gas bulging pressure inside the battery, and can solve the shortcomings of the previous battery bulging prevention technology such as high cost and affecting battery performance.

[0013] According to an embodiment of the present invention, the method may further include at least one of the following additional technical features:

[0014] According to an embodiment of the present invention, the alkylating agent is one of a halide, an alkylaluminum agent, an alkylmagnesium agent or an alcohol.

[0015] According to an embodiment of the present invention, the volume ratio of the alkylating agent to the mass ratio of the p-dibrombenzyl is (10 mL-15 mL): 1 g.

[0016] According to an embodiment of the present invention, the temperature of the preheating treatment is 35-45°C.

[0017] According to an embodiment of the present invention, the preheating treatment takes 40-60 minutes.

[0018] According to an embodiment of the present invention, the catalyst is one of anhydrous aluminum chloride, ferric chloride, boron trifluoride, zinc dichloride, and titanium tetrachloride.

[0019] According to an embodiment of the present invention, the mass ratio of p-dibromobenzene to the catalyst is (4-6):1.

[0020] According to an embodiment of the present invention, the temperature of the Friedel-Crafts alkylation reaction is 80-100°C.

[0021] According to an embodiment of the present invention, the Friedel-Crafts alkylation reaction time is 8-12 hours.

[0022] According to an embodiment of the present invention, the imidazolium bromide is selected from one of 1-decyl-3-methylimidazolium bromide, 1-octyl-3-methylimidazolium bromide and 1-hexyl-3-methylimidazolium bromide;

[0023] According to an embodiment of the present invention, the solvent is selected from one of ethanol, isopropanol, ethyl acetate or toluene.

[0024] According to an embodiment of the present invention, the mass ratio of the porous precursor to the volume of the solvent is 1 g: (10-15) mL.

[0025] According to an embodiment of the present invention, the temperature of the nucleophilic substitution reaction is 70-80°C.

[0026] According to an embodiment of the present invention, the time of the nucleophilic substitution reaction is 6-8 hours.

[0027] According to an embodiment of the present invention, the molar ratio of the porous precursor to the imidazolium bromide is 1:(1.1-1.3).

[0028] According to an embodiment of the present invention, the alkaline solution is a potassium hydroxide solution, a sodium hydroxide solution or a magnesium hydroxide solution.

[0029] According to an embodiment of the present invention, the concentration of the alkaline solution is 0.6-1.2 mol / L.

[0030] According to an embodiment of the present invention, the temperature of the ion exchange reaction is 40-50°C.

[0031] According to an embodiment of the present invention, the ion exchange reaction time is 2-3 hours.

[0032] In one aspect of the present invention, the present invention proposes a method for preparing a functional lithium battery positive electrode AT9 coating additive material. According to an embodiment of the present invention, the functional lithium battery positive electrode AT9 coating additive material is formed from a dibromide benzyl raw material through a Friedel-Crafts alkylation reaction to form a porous precursor; the porous precursor undergoes a nucleophilic substitution reaction with an imidazole bromide salt to generate an imidazole-modified porous precursor, the imidazole-modified porous precursor has abundant mesoporous / microporous channels and has the ability to enrich carbon dioxide; the imidazole-modified porous precursor is then subjected to an ion exchange reaction to remove bromide ions to obtain the AT9 coating additive material.

[0033] In another aspect of the present invention, the present invention also proposes a method for preparing the functional lithium battery positive electrode AT9 coating additive material of the present invention. According to an embodiment of the present invention, the method steps are as follows:

[0034] 1. In a nitrogen atmosphere, dissolve p-dibrombenzyl in an alkylating agent, stir and preheat for a period of time, add a catalyst, and heat to the temperature required for Friedel-Crafts alkylation to react. After the reaction is completed, centrifuge, wash and dry the solid-liquid mixture in the reaction bottle to obtain a porous precursor;

[0035] 2. The porous precursor obtained in 1 and imidazole bromide are dissolved in a solvent, and a nucleophilic substitution reaction is carried out under heating and stirring conditions. After the reaction is completed, the solid-liquid mixture in the reaction bottle is centrifuged, washed and dried to obtain an imidazole-modified porous precursor;

[0036] 3. The imidazole-modified porous precursor obtained in step 2 is placed in an excess alkaline solution, and an ion exchange reaction is carried out under heating and stirring conditions. After the reaction is completed, the solid-liquid mixture in the reaction bottle is centrifuged, washed and dried to obtain the AT9 coating additive material. The obtained additive material is subjected to elemental analysis, TEM, and BET characterization.

[0037] According to an embodiment of the present invention, the method may further include at least one of the following additional technical features:

[0038] According to an embodiment of the present invention, in 1, the alkylating agent is one of a halide, an alkylaluminum reagent, an alkylmagnesium reagent or an alcohol.

[0039] According to an embodiment of the present invention, in 1, the volume ratio of the alkylating agent to the mass ratio of p-dibrombenzyl is 10mL-15mL:1g.

[0040] According to an embodiment of the present invention, in 1, the preheating temperature is 35-45° C., and the preheating time is 40-60 minutes.

[0041] According to an embodiment of the present invention, in 1, the catalyst is one of anhydrous aluminum chloride, ferric chloride, boron trifluoride, zinc dichloride, and titanium tetrachloride.

[0042] According to an embodiment of the present invention, in 1, the mass ratio of p-dibromobenzene to the catalyst is 4-6:1.

[0043] According to an embodiment of the present invention, in 1, the Friedel-Crafts alkylation reaction temperature is 80-100° C., and the reaction time is 8-12 hours.

[0044] According to an embodiment of the present invention, in 2, the imidazolium bromide is one of 1-decyl-3-methylimidazolium bromide, 1-octyl-3-methylimidazolium bromide and 1-hexyl-3-methylimidazolium bromide.

[0045] According to an embodiment of the present invention, in 2, the solvent is one of ethanol, isopropanol, ethyl acetate and toluene.

[0046] According to the embodiment of the present invention, in 2, the volume ratio of the porous precursor mass to the solvent is 1g:10-15mL.

[0047] According to Example 2 of the present invention, the nucleophilic substitution reaction temperature is 70-80° C., and the reaction time is 6-8 hours.

[0048] According to the embodiment of the present invention, in 2, the molar ratio of the porous precursor to the imidazolium bromide is 1:1.1-1.3.

[0049] According to an embodiment of the present invention, in 3, the alkaline solution is a potassium hydroxide solution, a sodium hydroxide solution, or a magnesium hydroxide solution, and the concentration of the alkaline solution is 0.6-1.2 mol / L.

[0050] According to Example 3 of the present invention, the temperature of the ion exchange reaction is 40-50° C., and the reaction time is 2-3 hours.

[0051] In another aspect of the present invention, the present invention also provides a functional lithium battery positive electrode AT9 coating additive material. According to an embodiment of the present invention, the functional lithium battery positive electrode AT9 coating additive material is prepared according to the method described above.

[0052] In another aspect of the present invention, the present invention also proposes the use of the above-mentioned functional lithium battery positive electrode AT9 coating additive material in lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0054] Figure 1 The present invention is a roadmap for the preparation and application of the additive of catalyst embodiment 1; the porous nanocatalyst is prepared by Friedel-Crafts alkylation reaction, nucleophilic substitution reaction and ion exchange reaction, and the pores rich in additives can enrich CO2, and can be used as an additive in the positive electrode AT9 coating to alleviate the battery bulging phenomenon;

[0055] Figure 2 This is a TEM image of the catalyst of Example 1 of the catalyst of the present invention; it can be seen from the figure that the diameter of the additive is about 10-20nm, and due to the strong adsorption force generated by the high specific surface area of ​​the nanoparticles, it is aggregated into a cluster of solid particles. DETAILED DESCRIPTION

[0056] The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0057] Embodiment 1

[0058] A method for preparing the functional lithium battery positive electrode AT9 coating additive material of the present invention, the method steps are as follows:

[0059] Step 1: In a nitrogen atmosphere, dissolve p-dibromobenzyl in dichloroethane reagent, the volume of dichloroethane reagent and the mass ratio of p-dibromobenzyl is 12mL:1g. Stir and heat to 40°C, preheat for 50 minutes, add catalyst ferric chloride, wherein the mass ratio of p-dibromobenzene to ferric chloride is 5:1, heat to 90°C for Friedel-Crafts alkylation reaction for 10 hours, after the reaction is completed, centrifuge, wash and dry the solid-liquid mixture in the reaction bottle to obtain a porous precursor.

[0060] Step 2: The porous precursor obtained in step 1 and 1-octyl-3-methylimidazolium bromide are dissolved in isopropanol solvent (wherein the mass ratio of the porous precursor to the isopropanol solvent is 1 g:12 mL, and the molar ratio of the porous precursor to 1-octyl-3-methylimidazolium bromide is 1:1.2), and a nucleophilic substitution reaction is carried out at 75°C for 8 hours. After the reaction, the solid-liquid mixture in the reaction bottle is centrifuged, washed and dried to obtain an imidazole-modified porous precursor.

[0061] Step 3: The imidazole-modified porous precursor obtained in step 2 is placed in an excess of 1 mol / L sodium hydroxide solution, and an ion exchange reaction is carried out at 40° C. for 2.5 hours under stirring conditions. After the reaction is completed, the solid-liquid mixture in the reaction bottle is centrifuged, washed and dried to obtain the AT9 coating additive material. The obtained additive material is subjected to elemental analysis, TEM, and BET characterization.

[0062] In order to accurately evaluate the carbon dioxide gas enrichment ability of the AT9 coating additive material, the following experiment was designed:

[0063] 1. A double-container absorption device was used as the experimental device, in which the storage container and the absorption container were placed in a constant temperature water bath to maintain the temperature at a predetermined value.

[0064] 2. Place the AT9 coating additive material in an absorption vessel and evacuate it. Then, the carbon dioxide from the storage vessel is introduced into the absorption vessel and absorbed by it. When the pressure in both vessels drops, it indicates that the carbon dioxide has been captured. The molar amount of carbon dioxide absorbed can be calculated from the pressure change.

[0065] The calculation formula is:

[0066]

[0067] in,

[0068] V S 、V A and V D represent the volumes of storage container, absorption container and AT9 coating additive material respectively;

[0069] P0, P V and P represent the initial pressure of the storage vessel, the vapor pressure of the absorbent, and the pressure inside the vessel during the absorption process, respectively;

[0070] R is the gas constant and T is the temperature of the system.

[0071] In order to intuitively evaluate the practical application capabilities of the AT9 coating additive material, the following experiment was designed:

[0072] 1. Boehmite and AT9 coating additive material are made into battery AT9 coating material in a certain ratio, and the positive electrode sheet coated with this material and other main materials are made into soft-pack batteries. A certain volume of carbon dioxide is filled into the special soft-pack battery before packaging to test its thickness.

[0073] 2. Let it sit for a while and measure its thickness again.

[0074] Embodiment 2

[0075] The difference between Example 2 and Example 1 is that in step 2, 1-octyl-3-methylimidazolium bromide is replaced by 1-hexyl-3-methylimidazolium bromide, and other steps, parameters and raw materials remain unchanged.

[0076] Embodiment 3

[0077] The difference between Example 3 and Example 1 is that in step 2, 1-octyl-3-methylimidazolium bromide is replaced by 1-decyl-3-methylimidazolium bromide, and the other steps, parameters and raw materials remain unchanged.

[0078] Comparative Example 1

[0079] The difference between Comparative Example 1 and Example 1 is that in step 1, the reaction temperature of the Friedel-Crafts alkylation reaction is adjusted to 150° C., and the other steps, parameters and raw materials remain unchanged.

[0080] Comparative Example 2

[0081] The difference between Comparative Example 2 and Example 1 is that in step 1, the reaction temperature of the Friedel-Crafts alkylation reaction is adjusted to 50° C., and the other steps, parameters and raw materials remain unchanged.

[0082] Comparative Example 3

[0083] The difference between Comparative Example 3 and Example 1 is only that in step 1, the mass ratio of p-dibromobenzene to ferric chloride is 20:1, and the other steps, parameters and raw materials remain unchanged.

[0084] Comparative Example 4

[0085] The only difference between Comparative Example 4 and Example 1 is that in step 2, the molar ratio of the porous precursor to 1-octyl-3-methylimidazolium bromide is adjusted to 1:0.8, and the other steps, parameters and raw materials remain unchanged.

[0086] Comparative Example 5

[0087] The only difference between Comparative Example 5 and Example 1 is that in step 3, the concentration of sodium hydroxide is adjusted to 0.6 mol / L, the ion exchange reaction time is adjusted to 0.5 hour, and the other steps, parameters and raw materials remain unchanged.

[0088] Table 1 shows the additive properties and additive adsorption performance data of Examples 1-3 and Comparative Examples 1-5.

[0089]

[0090] Analyzing the data in Table 1, the AT9 additives prepared in Examples 1 to 3 show significant advantages in performance. These additives not only have a high content of imidazole loading (nitrogen content reaches 5-7%), but also have an excellent porous structure with a specific surface area far exceeding 700m 2 / g, which lays a solid foundation for the strong carbon dioxide adsorption capacity. Particularly outstanding is Example 1, whose carbon dioxide adsorption capacity is as high as 0.3153mmol / g. This outstanding performance effectively reduces the thickness of the soft-pack battery by 5.3mm in practical applications, fully demonstrating the remarkable effect of the additive in alleviating the battery bulging phenomenon. In contrast, the additives in the comparative examples exhibited weaker performance due to different problems in the synthesis process. Comparative Example 1 has damaged pore structure and limited adsorption capacity due to excessively high reaction temperature; Comparative Examples 2 and 3 have incomplete pore development due to insufficient reaction conditions, which also affects their adsorption efficiency; the reduction in the amount of imidazole bromide in Comparative Example 4 directly leads to a decrease in nitrogen content and adsorption capacity; and Comparative Example 5 has incomplete bromine replacement due to insufficient ion exchange reaction, which further weakens its adsorption capacity.

[0091] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0092] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a functional lithium battery positive electrode AT9 coating additive material, characterized in that: include: S1: preheating p-dibrombenzyl and an alkylating agent, then adding a catalyst to perform a Friedel-Crafts alkylation reaction to obtain a porous precursor; S2: dissolving the porous precursor and imidazole bromide in a solvent, and performing a nucleophilic substitution reaction to obtain an imidazole-modified porous precursor; S3: placing the imidazole-modified porous precursor in an alkaline solution to perform an ion exchange reaction to obtain a functional lithium battery positive electrode AT9 coating additive material.

2. The method according to claim 1, characterized in that The alkylating agent is one of an alkyl halide, an alkyl aluminum reagent, an alkyl magnesium reagent or an alcohol; Optionally, the volume of the alkylating agent and the mass ratio of the p-dibrombenzyl are (10 mL-15 mL): 1 g.

3. The method according to claim 1, characterized in that The temperature of the preheating treatment is 35-45°C; Optionally, the preheating treatment lasts for 40-60 minutes.

4. The method according to claim 1, characterized in that The catalyst is one of anhydrous aluminum chloride, ferric chloride, boron trifluoride, zinc dichloride, and titanium tetrachloride; Optionally, the mass ratio of p-dibromobenzene to the catalyst is (4-6):

1.

5. The method according to claim 1, characterized in that The temperature of the Friedel-Crafts alkylation reaction is 80-100°C; Optionally, the Friedel-Crafts alkylation reaction time is 8-12 hours.

6. The method according to claim 1, characterized in that The imidazolium bromide is selected from one of 1-decyl-3-methylimidazolium bromide, 1-octyl-3-methylimidazolium bromide and 1-hexyl-3-methylimidazolium bromide; Optionally, the solvent is selected from one of ethanol, isopropanol, ethyl acetate or toluene; Optionally, the mass of the porous precursor and the volume ratio of the solvent are 1 g: (10-15) mL; Optionally, the temperature of the nucleophilic substitution reaction is 70-80°C; Optionally, the nucleophilic substitution reaction time is 6-8 hours; Optionally, the molar ratio of the porous precursor to the imidazolium bromide salt is 1:(1.1-1.3).

7. The method according to claim 1, characterized in that The alkaline solution is potassium hydroxide solution, sodium hydroxide solution or magnesium hydroxide solution; Optionally; the concentration of the alkaline solution is 0.6-1.2 mol / L.

8. The method according to claim 1, characterized in that The temperature of the ion exchange reaction is 40-50°C; Optionally, the ion exchange reaction time is 2-3 hours.

9. A functional lithium battery positive electrode AT9 coating additive material, characterized in that: The functional lithium battery positive electrode AT9 coating additive material is prepared by the method according to any one of claims 1-8.

10. Application of the functional lithium battery positive electrode AT9 coating additive material according to claim 9 in lithium batteries.

Citation Information

Patent Citations

  • Lithium ion battery electrolyte solution and preparation method thereof, and lithium ion battery

    CN105810997A

  • Lithium ion battery opening formation method and lithium ion battery

    CN114284562A

  • Nano-catalyst for synthesizing dimethyl carbonate as well as preparation method and application of nano-catalyst

    CN117884175A

  • Porous nano-catalyst for synthesizing propylene carbonate as well as preparation method and application of porous nano-catalyst

    CN118580407A